1986
DOI: 10.1177/074193258600700608
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Employment for Adults with Developmental Disabilities

Abstract: The role of employment in the lives of young adults and adults with developmental disabilities has received a considerable amount of attention during the past few years. This study attempted to document the movement of this population into the areas of competitive employment. A survey of 1,629 facilities and organizations throughout the U.S. revealed that more developmentally disabled persons are being hired in competitive employment settings, and that job retention is good. Further, the data confirm that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…Although Wehman (no date) and Kiernan et al (1988) reported relatively high earnings among supported employees, the average annual earnings reported in Illinois were under $2,000, considerably below those that could be inferred from the Wehman and Kiernan et al data. Since earnings in supported employment were only 37% higher than those in alternative placements, the increase in earnings attributable to supported employment in Illinois amounted to only $710 per year.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Although Wehman (no date) and Kiernan et al (1988) reported relatively high earnings among supported employees, the average annual earnings reported in Illinois were under $2,000, considerably below those that could be inferred from the Wehman and Kiernan et al data. Since earnings in supported employment were only 37% higher than those in alternative placements, the increase in earnings attributable to supported employment in Illinois amounted to only $710 per year.…”
contrasting
confidence: 56%
“…According to another recent survey of rehabilitation agencies and facilities providing employment services for adults with developmental disabilities (Kiernan, McGauphey, Schalock, & Rowland, 1988), almost 16,500 persons were placed in transitional, supported, or competitive jobs in 1986. Of those working in transitional, supported, or competitive jobs, about half worked part time and the other half full time.…”
mentioning
confidence: 99%
“…For example, an investigation of 1,411 supported employees in eight states showed that 10% of employees labeled "mentally retarded" were identified as severely or profoundly mentally retarded (less than 8% of the total number of supported employees); 38% were moderately mentally retarded, 45% were mildly retarded, and 11% were borderline mentally retarded . Other studies of national supported employment outcomes corroborate the finding that less than 8% of those served in supported employment are persons with severe handicaps (Kiernan et al, 1986;Rusch et al, in press;Wehman et al, 1989). Although persons with severe handicaps constitute only a small proportion ofthe total supported employee population, an even smaller number of persons with the behavioral characteristics indicative of severe handicaps (e.g., ambulation impairments, fine-motor impairments, challenging behaviors) are being served nationally in supported employment programs ).…”
Section: Supported Employment Programmentioning
confidence: 72%
“…Populations served. In spite of the dear benefits of the supported employment model, recent investigations of outcome data from supported employment programs throughout the United States indicate that few individuals with severe handicaps (the target population to be served by supported employment) are being employed with support (Kiernan, McGaughey, & Schalock, 1986; press; Wehman, Kregel, & Shafer, 1989; press). For example, an investigation of 1,411 supported employees in eight states showed that 10% of employees labeled "mentally retarded" were identified as severely or profoundly mentally retarded (less than 8% of the total number of supported employees); 38% were moderately mentally retarded, 45% were mildly retarded, and 11% were borderline mentally retarded .…”
Section: Supported Employment Programmentioning
confidence: 99%
“…These imperatives emerged in response to abundant evidence that existing educational services for adolescents and young adults were ineffective in producing desired employment and community participation outcomes Edgar, 1987;Kiernan & Ciborowski, 1986;Wehman, 1992).…”
mentioning
confidence: 99%